Mechanical properties characterisation of welded joint of austenitic stainless steel using instrumented indentation technique. (3rd May 2016) - Wu, S.; Xu, T.; Song, M.; Guan, K.
Abstract: The instrumented indentation test is a promising nondestructive technique for evaluating mechanical properties of metallic materials. In this study, the localised mechanical properties of welded joint of 304 austenitic stainless steel were characterised with the instrumented indentation test. The single V-groove welded joint was produced using the electric arc welding. A series of instrumented indentation tests were carried out at different regions, including base material, weld zone and heat-affected zone (HAZ). A soft zone regarding strength properties was found in the coarse-grain HAZ. The results show that the HAZ has the lowest yield strength and tensile strength (263.6 MPa, 652.5 MPa) compared with the base material (307.4 MPa, 807.9 MPa) and the weld zone (285.6 MPa, 702.1 MPa). In addition, characterisations of microstructure, microhardness and conventional tensile tests have been performed for comparison. The results reveal that the localised mechanical properties of welded joint of austenitic stainless steel can be represented effectively with the instrumented indentation technique.